A cadeia de lucro em servi??os e o uso do modelo DART: as influ??ncias da cocria????o de valor no comportamento dos clientes de servi??os - Mangini, Eduardo Roque (2019)
Service-dominant logic is a new marketing approach. Its premises and axioms involve the relationship between customer and service provider. From this interaction occurs the Value Cocreation (VCC) process. To evaluate VCC the DART Model was used. In VCC the customer starts to take an active participation in the Service production. So, customers are considered business resource. However, the VCC and customer behavior is still unknown. To verify the relationship between VCC and behavioral consequences, three studies were carried out involving customers of banking, mobile phone, and higher education. The choice of these services lies in the fact that they are considered mass services, with similarities and differences between them. From the survey as a research method, the orientation was of positivist nature with modeling of structural equations. Data were collected by an online platform and resulted in 322 customers of banking services, 311 customers of mobile phone services and 379 customers of higher education, all in the Brazilian context. The data were initially treated and analyzed using the SPSS 22 statistical package. Besides the checks involving descriptive statistics, the Mahalanobis Distance Test, Harman???s Single Factor, and Normality Test were performed. Next, the Structural Equation Modeling was performed using the SmartPLS 3.2.7 software. The analyzes have allowed evaluating the relationships between VCC (DART model), Trust (Affective and Cognitive) and Satisfaction. The VCC process occurred in all services analyzed, and it showed a positive and significant relationship with Satisfaction and Trust. In addition, the predictive role of Satisfaction and Trust in the formation of Loyalty was evaluated. It was possible to confirm the positive and statistically significant relationship between Satisfaction and Loyalty. Cognitive Trust as a predictor of Loyalty has proved significant in banking and mobile phone services. Affective Trust had a predictive role of Loyalty in educational services. In general, it was possible to verify similarities and differences among the customers of the chosen services. It was also possible to demonstrate the importance of VCC and the active participation of the customer in the process, which influences the entire strategic and market aspect of the companies that provide services.